Enhancing socio-communicative functions in an MCI patient with intra-nasal insulin: a case report - Schatz, Sara; Gutiérrez, Grace Rose (Frontiers in Psychiatry, 2024)
This report examines extended intra-nasal insulin treatment [INI] for an Insulin Resistant early Mild Cognitive Impairment [MCI] patient. Patient [EJ] also had medial temporal lobe [MTL] damage, poor short-term memory, significant irritability, and social and linguistic withdrawal at treatment start. Compared to baseline, nine months INI treatment increased grey matter volume, lowered beta-amyloid levels, and improved MCI and FAS scores. Patient also increased pragmatic capacities in social conversation and procedural memory. These findings align with results from prior clinical trials on INI and suggest that treatment can slow neurodegenerative disease progression in early MCI patients.